A Study on Entrepreneurial Behaviour of Dairy Farmers - B. L. Pisure , B. M. Thombre andC. R. Jamadar (Indian Journal of Extension Education, 2014)
Taking into account the importance of developing entrepreneurial behaviour of dairy farmers, the present investigation was undertaken in Latur district of Maharashtra. Asample of 120 dairy farmers were selected from the district following a multistage random sampling procedure. It was observed that majority of the dairy farmers under study were from medium dairy farming experience having secondary school level of education along with semi-medium and medium land holding. Majority of the respondents had small family size medium level of annual income, herd size, social participation, extension contact, market orientation, and use of sources of information. Majority of the respondents were under medium level of entrepreneurial behaviour. On calculation of Entrepreneurial Behaviour Index (EBI) of the dairy farmers, majority of the respondents belonged to low category of entrepreneurial behavior.